Inclusion, Exclusion and Isolation of Autistic People: Community Attitudes and Autistic People's Experiences. - Jones, Sandra C.; Gordon, Chloe S.; Akram, Muhammad; Murphy, Nicole; Sharkie, Fiona (Journal of Autism & Developmental Disorders, 2022)
There is limited research examining the inclusion of autistic people in their local communities. This paper reports on two Australian studies which explored this gap, focusing on both autistic people's experiences and non-autistic people's attitudes towards autistic individuals. Study One was conducted with primarily non-autistic people (n = 2,383), and Study Two with primarily parents and carers of autistic people (n = 1,297 people). The majority of non-autistic adults perceived discrimination against autistic people in the community; consistent with the experiences of autistic people and their carers. Of particular concern was more negative attitudes towards, and experiences of, autistic adults. There is an urgent need to improve society's acceptance and inclusion of autistic people of all ages.